Temporal space distribution of abiotic and biotic parameters in an amazon estuary (Brazil) - Santos, Arielly Siqueira dos; Sousa, Pedro Henrique Campos; Melo, Nuno Filipe Alves Correia de; Mesquita, Karina Ferreira Castro; Pereira, José Almir Rodrigues; Souza Santos, Maria de Lourdes (Arquivos de Ciências do Mar, 2020)
The objective of this work was to evaluate the distribution of abiotic parameters (temperature, salinity, pH, dissolved oxygen, dissolved oxygen saturation rate, suspended material, N-ammoniacal, nitrite, nitrate, phosphate, and silicate) and biotic (chlorophyll a) in relation to the climatic periods of the Amazon region in the Guajará-Mirim estuary, which is located in Vigia, Pará. Water collection for the analysis of abiotic and biotic parameters occurred in the months of September and November of 2011 and January, March, May, and July of 2012. The distribution of abiotic and chlorophyll a parameters in the Guajará-Mirim estuary is influenced by periods of both greater and lesser rainfall, which is also indicated by the analysis of the main components. The saturation rate of dissolved oxygen in the study period classified the area as a zone of low saturation without a pollution zone. In addition, the average value of dissolved oxygen for this area exceeded the value established by Conama nº 357/2005 for the classification of bodies of water. The findings revealed that the majority of N-ammoniacal and nitrate concentrations also exceeded this value, which indicates the need for more detailed monitoring to assess the diffuse sources of pollution in this estuary. With this information, mitigation measures can be proposed to maintain the water quality in this environment, which is crucial for the local population.